Association between dietary choline intake and bone mineral density in adolescents: a NHANES-based study - Keyi Li; Chunhong Guo; Yishan Yin; Zefeng Zhu (BMC Pediatrics, 2025)
Abstract Introduction Dietary choline has been implicated in bone health, but its association with bone mineral density (BMD) in adolescents remains unclear. This study examines the relationship between dietary choline intake and BMD in adolescents aged 12–19 years. Materials and methods This cross-sectional study included 2,531 adolescents from the NHANES 2005–2010 dataset, using weighted analyses to account for complex survey design. Dietary choline intake was assessed from two-day dietary recall data, and BMD for the lumbar spine and femur was measured by dual-energy X-ray absorptiometry (DXA). Multivariate regression models adjusted for relevant covariates. Subgroup analyses explored effect modifiers, and a sensitivity analysis with multiple imputation for missing covariates confirmed the stability of results. Results Higher dietary choline intake was significantly associated with increased BMD in both the lumbar spine and femoral regions. For each 100 mg/day increase in choline intake, lumbar spine BMD increased by β = 6.75 (95% CI: 0.79–12.70, P = 0.028), and femoral BMD by β = 10.93 (95% CI: 3.58–18.27, P = 0.005). Participants in the highest choline intake tertile (T3) showed significantly higher BMD in the lumbar spine (β = 18.72, 95% CI: 1.84–35.60, P = 0.031) and femur (β = 28.33, 95% CI: 5.03–51,63, P = 0.020). The subgroup analyses indicated no significant interactions across subgroups, confirming the stability of the results. Additionally, sensitivity analyses conducted following multiple imputations of missing covariate data supported these findings. Conclusions Higher dietary choline intake is positively associated with BMD in adolescents, supporting the potential role of choline in bone health during this critical developmental period.